Prophetic Literacy Education: An Integrative Model of Spirituality, Intellectuality, and Social Action - Ajhuri, Kayyis Fithri (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study aims to explore a literacy model based on religious values as implemented by the Komunitas Kutub Yogyakarta/Kutub Yogyakarta Community (KKY) and the Forum Penulis Muda Ponorogo (FPM). Prophetic literacy in this study is defined as a literacy approach that integrates three main pillars: spirituality, intellectuality, and social action. Using the Community-Based Research (CBR) method, this study involved active participation from the communities through in-depth interviews, participatory observations, and document analysis. The findings reveal that KKY develops spirituality-based literacy through activities such as Qur’anic recitation, dhikr, and religious studies. Meanwhile, the intellectuality aspect is enhanced through scientific discussions and literary studies, which are relevant for improving critical thinking skills. In the social action pillar, KKY excels through literacy outreach programs and independent entrepreneurship development. On the other hand, FPM emphasizes thematic discussions, such as book and essay discussions, as well as social action realized through literacy outreach programs and literary performances. This prophetic literacy model is relevant for implementation in both formal and non-formal education as part of efforts to develop holistic character education based on religious values. Prophetic literacy not only builds technical literacy skills but also instills the values of humanization, liberation, and transcendence, which are essential for addressing the challenges of globalization. This study recommends integrating this model into literacy curricula, providing training for educators, and establishing literacy communities as a medium for character education. Thus, literacy based on religious values can serve as a strategic approach to supporting the development of a generation with excellent character